Integrating Stability Assessments Under the Financial Sector Assessment Program into Article IV Surveillance : Revised Proposed Decision. (Policy Papers; Policy Paper, 2010)
Recognizing the important impact that a member's domestic economic and financial policies can have on systemic stability, Article IV of the IMF's Articles of Agreement establishes obligations for members respecting the conduct of these policies, including their financial sector policies. An examination of members' financial sector policies is important in all cases of bilateral surveillance, and three quarters of the Fund's membership has already undergone a financial stability assessment. With this Decision, the Fund decides that, taking into account the framework described above and the overall purpose of surveillance, heightened scrutiny should be given in bilateral surveillance to the financial sector policies of those members whose financial sectors are systemically important, given the risk that domestic and external instability in such countries will lead to particularly disruptive exchange rate movements and undermine systemic financial and economic stability. The mandatory financial stability assessments undertaken under this Decision will consist of the following elements: a) an evaluation of the source, probability, and potential impact of the main risks to macro-financial stability in the near-term for the relevant financial sector; b) an assessment of the authorities' financial stability policy framework; and c) an assessment of the authorities' capacity to manage and resolve a financial crisis should the risks materialize.